Update on gold nanoparticles from cathedral windows to nanomedicine - Voliani, Valerio (ISmithers Rapra Pub., 2013)
In the last decade, gold nanoparticles have provided a suitable platform for the development of novel and efficient diagnostic and therapeutic tools, which avoid the typical drawbacks of the old systems. They are biocompatible and they can be easily synthesised, encapsulated and functionalised with (bio)molecules. Nanoparticles produced by a wet chemistry synthesis have the geometry, which enables the complete control of their optical and physical properties. It is also possible to influence the targeting and stability/release behaviour by coating the nanoparticle surface. In this Update the r.